The role of genes, intelligence, personality, and social engagement in cognitive performance in Klinefelter syndrome. Issue 3 (9th February 2017) - Skakkebæk, Anne; Moore, Philip J.; Pedersen, Anders Degn; Bojesen, Anders; Kristensen, Maria Krarup; Fedder, Jens; Laurberg, Peter; Hertz, Jens Michael; Østergaard, John Rosendahl; Wallentin, Mikkel; Gravholt, Claus Højbjerg
Abstract: Introduction: The determinants of cognitive deficits among individuals with Klinefelter syndrome (KS) are not well understood. This study was conducted to assess the impact of general intelligence, personality, and social engagement on cognitive performance among patients with KS and a group of controls matched for age and years of education. Methods: Sixty‐nine patients with KS and 69 controls were assessed in terms of IQ, NEO personality inventory, the Autism Spectrum Quotient (AQ) scale, and measures of cognitive performance reflecting working memory and executive function. Results: Patients with KS performed more poorly on memory and executive‐function tasks. Patients with KS also exhibited greater neuroticism and less extraversion, openness, and conscientiousness than controls. Memory deficits among patients with KS were associated with lower intelligence, while diminished executive functioning was mediated by both lower intelligence and less social engagement. Conclusion: Our results suggest that among patients with KS, memory deficits are principally a function of lower general intelligence, while executive‐function deficits are associated with both lower intelligence and poorer social skills. This suggests a potential influence of social engagement on executive cognitive functioning (and/or vice‐versa) among individuals with KS, and perhaps those with other genetic disorders. Future longitudinal research would be important to further clarify this and other issues discussed in this research. Abstract : Among patients with Klinefelter syndrome, memory deficits are principally a function of lower general intelligence, while executive‐function deficits are associated with both lower intelligence and poorer social skills. This suggests a potential influence of social engagement on executive cognitive functioning (and/or vice‐versa) among individuals with Klinefelter syndrome.